Optimizing Canang Flower Waste Extract for Staining Fasciolopsis buski Eggs: An Enhancement of the Kato-Katz Method - I Komang Tri Yasa Widnyana; Kadek Indira Maheswari; Putu Sathiya Adi Janendra; Dewa Gede Putra Mahayana; Indra Dwisaputra; Made Bayu Permasutha; Irma Rahmayani; Pasala, Metamalik (Biosaintifika: Journal of Biology & Biology Education, 2025)
Fasciolopsis buski is a parasitic helminth that can infect humans. Diagnosing helminthiasis can be confirmed through fecal testing utilizing the Kato-Katz method.  The Kato-Katz method employs methylene blue staining, which poses environmental hazards due to its carcinogenic characteristics. An alternative to staining is the use of a canang, a common Balinese item used for prayers. The utilized waste canang flowers were Tagetes erecta, Impatiens balsamina (red), and Impatiens balsamina (purple). The research began with an extraction procedure that involved cutting the flowers into small pieces, resulting in approximately 500 grams of fragments. The flower components were macerated in two liters of 96% ethanol for five days. Additionally, cellophane immersion of the extracted findings was performed. The findings indicated that each sample from the three treatment groups (T1, 1%; T2, 2%; and T3, 3%) and the two control groups.  Sub-analysis testing evaluated the quantity of helminth eggs, quantified as eggs per gram of feces via field-of-view observation. The T3 (3%) exhibited results that were not statistically significantly different (P>0.05) from the positive control group. The T3 (3%) test provides the most favorable and optimal results as a substitute for methylene blue in microscopic staining evaluations.